Characterization of Early Inflammatory Events Leading to Provoked Vulvodynia Development in Rats - Awad-Igbaria Y; Dadon S; Shamir A; Livoff A; Shlapobersky M; Bornstein J; Palzur E (Journal of Inflammation Research, 2022)
Yaseen Awad-Igbaria,1,2 Shilo Dadon,1,2 Alon Shamir,3,4 Alejandro Livoff,5 Mark Shlapobersky,5 Jacob Bornstein,1,2,* Eilam Palzur2,* 1Faculty of Medicine in the Galilee, Bar-Ilan University, Safed, Israel; 2The Research Institute of Galilee Medical Center, Nahariya, Israel; 3Psychobiology Research Laboratory, Mazor Mental Health Center, Akko, Israel; 4The Ruth and Bruce Rappaport Faculty of Medicine, Technion – Israel Institute of Technology, Haifa, Israel; 5Pathology Department, Barzilai University Medical Center, Ashkelon, Israel*These authors contributed equally to this workCorrespondence: Yaseen Awad-Igbaria, The Research Institute of Galilee Medical Center, PO Box 21, Nahariya, 22100, Israel, Tel +972 50-4500101, Email Yaseenawad123@gmail.comBackground: Provoked vulvodynia (PV) is the main cause of vulvar pain and dyspareunia. The etiology of PV has not yet been elucidated. However, PV is associated with a history of recurrent inflammation, and its often accompanied by increases in the numbers of mast cells (MCs) and sensory hyperinnervation in the vulva. Therefore, this study aimed to examine the role of MCs and the early inflammatory events in the development of chronic vulvar pain in a rat model of PV.Methods: Mechanical and thermal vulvar sensitivity was measured for 5 months following zymosan vulvar challenges. Vulvar changes in glutamate and nerve growth factor (NGF) were analyzed using ELISA. Immunofluorescence (IF) staining of the vulvar section after 20, 81, and 160 days of the zymosan challenge were performed to test MCs accumulation, hyperinnervation, and expression of pain channels (transient receptor potential vanilloid/ankyrin-1-TRPV1 & TRPA1) in vulvar neurons. Changes in the development of vulvar pain were evaluated following the administration of the MCs stabilizer ketotifen fumarate (KF) during zymosan vulvar challenges.Results: Zymosan-challenged rats developed significant mechanical and thermal vulvar sensitivity that persisted for over 160 days after the zymosan challenge. During inflammation, increased local concentrations of NGF and glutamate and a robust increase in MCs degranulation were observed in zymosan-challenged rats. In addition, zymosan-challenged rats displayed sensory hyperinnervation and an increase in the expression of TRPV1 and TRPA1. Treatment with KF attenuated the upregulated level of NGF during inflammation, modulated the neuronal modifications, reduced MCs accumulation, and enhanced mechanical hypersensitivity after repeated inflammation challenges.Conclusion: The present findings suggest that vulvar hypersensitivity is mediated by MCs accumulation, nerve growth, and neuromodulation of TRPV1 and TRPA1. Hence, KF treatment during the critical period of inflammation contributes to preventing chronic vulvar pain development.Keywords: provoked vulvodynia, inflammation, mast cell, nerve growth factor, glutamate, hyperinnervation